musicalwatch
New member
- Joined
- Aug 22, 2013
- Messages
- 1
Question: Prove that if m|a and m|b, then gcd(a/m,b/m)=gcd(a,b)/m, provided that m>0.
Since m|a and m|b, a can be written as a=mt for some integer t. Likewise, b=mq for some integer q.
Therefore, we can rewrite the left part of gcd equation as gcd(mt/m,mq/m)=gcd(t,q)=tr+qs, where r and s are some integers.
The right part of the equation will become: gcd(a,b)/m = gcd(mt, mq)/m= mtr/m+mqs/m=tr+qs, where r and s are some integers
tr+qs=tr+qs..... I have a feeling that this proof isn't correct. After all, r, s, t, q are "some" integers so some of my statements are most likely wrong.
I also tried working with m|gcd(a,b) and gcd(a,b)=mx+my for all integers x and y but couldn't develop this thought.
Since m|a and m|b, a can be written as a=mt for some integer t. Likewise, b=mq for some integer q.
Therefore, we can rewrite the left part of gcd equation as gcd(mt/m,mq/m)=gcd(t,q)=tr+qs, where r and s are some integers.
The right part of the equation will become: gcd(a,b)/m = gcd(mt, mq)/m= mtr/m+mqs/m=tr+qs, where r and s are some integers
tr+qs=tr+qs..... I have a feeling that this proof isn't correct. After all, r, s, t, q are "some" integers so some of my statements are most likely wrong.
I also tried working with m|gcd(a,b) and gcd(a,b)=mx+my for all integers x and y but couldn't develop this thought.